THE EFFECT OF LEADERSHIP STYLE AND WORK ETHICS AGAINST IMPROVING EMPLOYEES PERFORMANCE AT PT PAPER FACTORY TJIWI KIMIA TBK. MOJOKERTO - Angga Martha Mahendra (Program Studi Manajemen STIE Kesuma Negara Blitar, 2019)
Leadership style, work ethic is an important factor in efforts to develop human resources and improve employee performance. Leaders play an important role in an organization. Leaders understand who is led and apply leadership styles that are appropriate to the conditions of their employees in order to improve performance. This study aims to examive whether there is Influence of Leadership Style and Work Ethics on Performance. The research method used quantitative descriptive. The total population of 600 and total samples of 60 respondents and data were analyzed by multiple regression. Samples were taken by random samplin g. The results showed partially the leadership style variables, work ethic has a significant effect on employee performance, while the simultaneous variables of leadership style (X1) and work ethic (X2) have no effect on employee performance. Key Words: leadership style, work ethic and employee performance